2015
DOI: 10.17219/acem/41028
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound at the Hand Phalanges in Adolescent Girls is Related to Their Overall Physical Fitness

Abstract: mal growth hormone and thyroid hormone secretion influence bone mass and mineralization. On the other hand, in the time of puberty, the physical activity of girls typically decreases, which can negatively influence bone mass. Various diseases can result in lower bone mass and size [3][4][5][6]. Worsened mechanical properties of bones were found, using ultrasound, in children and adolescents suffering from different diseases such as diabetes mellitus, chronic renal failure or leukemia survivors [7][8][9].The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…No statistically significant age-dependent differences between male twin pairs in bone parameters were observed. Chwałczyńska et al [ 28 ] and Bolanowski et al [ 29 ] confirmed that physical fitness and muscle strength were important factors influencing Ad-SoS values in adolescents; nevertheless, the impact was seen only in older boys and in all girls. This may confirm the hypothesis that due to the fact of an earlier pubertal age, females are increasingly susceptible, as well as at an earlier age, to bone remodelling changes.…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant age-dependent differences between male twin pairs in bone parameters were observed. Chwałczyńska et al [ 28 ] and Bolanowski et al [ 29 ] confirmed that physical fitness and muscle strength were important factors influencing Ad-SoS values in adolescents; nevertheless, the impact was seen only in older boys and in all girls. This may confirm the hypothesis that due to the fact of an earlier pubertal age, females are increasingly susceptible, as well as at an earlier age, to bone remodelling changes.…”
Section: Discussionmentioning
confidence: 99%
“…PA in post-menopausal women, especially several times a week, significantly influences bone health [105]. Bolanowski et al [117] assessed the ultrasound properties of the skeletal status (amplitude-dependent speed of sound-Ad-SoS) measured at hand phalanges in adolescent girls regarding the influence of pubertal status and the level of physical fitness. The statistically significantly higher results of the Ad-SoS were found in girls presenting the highest level of physical fitness than in girls with a minimal level of physical fitness.…”
Section: Skeletal Status Assessed With Qus and Pa And Non-combat Sportsmentioning
confidence: 99%
“…As a result, the score can be analysed by reference to the norms defined for the specific age groups relative to sex. Furthermore, it can also be used to make comparisons with the person's physical fitness at different times of life and with the achievements of other people [32,33]. The index comprises 6 trials: speed test, jumping ability test, arm strength test, flexibility test, endurance test and abdominal muscle test [34,35].…”
Section: Physical Fitness Measuresmentioning
confidence: 99%